EVALUATION OF THE DEVELOPMENT OF ATTITUDES AND CHARACTER OF ELEMENTARY SCHOOL STUDENTS THROUGH ASSESMENT OF AFFECTIVE ASPECTS - Tabita Theresia Nababan (STKIP PGRI Situbondo, 2025)
This study aims to analyze the effectiveness of affective assessment in evaluating the development of elementary students’ attitudes and character. The method used is a literature review with a qualitative descriptive approach. Instruments examined include observation, self-assessment, and peer assessment. Thematic analysis was applied to scientific literature from the past decade. Results show that affective assessment plays a crucial role in character formation, yet its implementation still faces challenges in instrument validity and teacher understanding. This research proposes a digital-based affective evaluation model that is more objective and participatory.